Injury incidence, mechanism and diagnosis in top-level teamgym: a prospective study conducted over one season - Harringe, M. L.; Renström, P.; Werner, S. (Scandinavian Journal of Medicine & Science in Sports, 2007)
The aim of this study was to evaluate injury incidence, mechanism and diagnosis in Swedish teamgym. Sixteen male and 26 female gymnasts with international experience were prospectively followed during one season of training and competition. Injuries leading to a modified participation or total absence from gymnastics during 1 week or more were registered. Twenty-seven of the 42 gymnasts sustained 42 injuries. The injury incidence was 2.2/1000 gymnastics hours. No gender differences were found. Sixty-two percent of the injuries were located to the lower extremity, 28.5% to the back and 9.5% to the upper extremity. The most common injury was ankle sprain and the most frequent mechanisms were joint compression and joint rotation. The majority of the injuries occurred in the landing phase of the gymnastics skills and 50% of the injuries were reported at the end of the training session. Eighteen injuries occurred while the gymnasts were in a negative state of mood such as stressed or afraid. Injury prevention programs should be developed with respect to these findings. Special emphasis must be placed on the landing phase of the gymnastics skills as this phase seems to be critical.